Evolution in Europe of African swine fever genotype II viruses from highly to moderately virulent - C, Gallardo; I, Nurmoja; A, Soler; V, Delicado; A, Simón; E, Martin; C, Perez; R, Nieto; M, Arias (Veterinary microbiology, 2018)
Since its arrival in the Caucasus and Russia in 2007, African swine fever virus (ASFV) has spread widely and has now affected the EU countries of Estonia, Latvia, Lithuania, Poland and, more recently, the Czech Republic and Romania. The ever-increasing evidence of seropositive wild boar in certain areas suggests that some animals may be surviving for some time or could even be recovering from the disease. This could be due to acquired immunity after the primary infection and/or the presence of related viruses of reduced virulence. To assess these hypotheses, two ASFV field strains from Estonia were studied in vivo in two groups of domestic pigs. After an incubation period of 4 ± 1.6 days, the pigs inoculated intramuscularly with Es15/WB-Tartu 14 ASFV (group 2) developed clinical signs associated with acute disease and succumbed 7 and 11 days post infection (dpi). Pigs inoculated with Es15/WB-Valga-14 ASFV (group 1) had longer incubation times (8 days) than those in group 2 and developed variable clinical signs and lesions compatible with subacute and chronic forms of ASF; they succumbed at 11 and 25 dpi. The in-contact pigs in both groups became infected 7-14 days after exposure and exhibited variable clinical manifestations and pathological findings ranging from acute to chronic disease. Two animals per group recovered completely after infection and were protected against a subsequent homologous virus challenge-exposure performed at 78 dpi. Under experimental conditions, no transmission occurred from the survivors to susceptible sentinel pigs housed together with the survivors 137 days after the primary infection.
Keywords: molekulární evoluce; Genotype II; African swine fever; Sus scrofa; Evropa; Evolution, Molecular; Polsko; Virulence; sérologické testy; séroepidemiologické studie; Genotype; zvířata; Europe; virulence; Poland; Viremia; Swine; African Swine Fever; Moderate virulence; delece genu; Gene Deletion; virus afrického moru prasat; Epidemiological Monitoring; Czech Republic; africký mor prasat; genotyp; epidemiologické monitorování; Serologic Tests; Animals; viremie; Česká republika; African Swine Fever Virus; prasata; Seroepidemiologic Studies